Characterization and properties of recycled polypropylene (RPP)/ Chloroprene Rubber (CR) blend - Nurul Azra Bakaruddin (School of Materials Engineering, 2011)
The primary objective of this study is to determine the feasibility of recycled polypropylene (RPP) in RPP/CR blends with different composition.